PENGARUH LEADER MEMBER EXCHANGE, PSYCHOLOGICAL CAPITAL, DAN HUMAN RESOURCE PRACTICES TERHADAP EMPLOYEE RESILIENCE MELALUI EMPLOYEE ENGAGEMENT - Sabrina, Salya Widya; Sutawidjaya, Ahmad Hidayat; Ramli, Abdul Haeba; Mariam, Siti (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the influence of Leader–Member Exchange, Psychological Capital, and Human Resource Practices on employee resilience, with employee engagement positioned as a mediating variable. The research was conducted at Universitas Terbuka Tangerang using a quantitative approach, involving a sample of 130 respondents. Data analysis was carried out using the Structural Equation Modeling (SEM) method through SmartPLS 4 software. The findings indicate that all three main variables significantly contribute to employee resilience. Furthermore, employee engagement is proven to act as a mediator that strengthens the relationships among these variables, confirming that optimizing workplace relationships and implementing effective HR policies are key to building resilience in the work environment. Theoretically, this research contributes to the development of organizational behavior studies, particularly regarding the role of Leader–Member Exchange, Psychological Capital, and Human Resource Practices in increasing employee resilience in the context of distance learning-based higher education organizations. Practically, the results of this study can serve as a basis for organizations in designing adaptive human resource management strategies by improving the quality of working relationships between leaders and employees, strengthening psychological capital, and optimizing human resource management practices to increase employee resilience in facing changes and work pressures.